Toxicological Aspects of Saccharin - Singh, Zorawar (Food Biology, 2013)
Saccharin is a widely used sweetener especially prescribed for the diabetics. But since its discovery, its use has been a matter of controversy due to its tumour promoting abilities in second generations of rats. As a result, saccharin was thought to be unfit for human consumption and was banned before the First World War. Later on, various studies focused on the possible mechanism of carcinogenic effects of saccharin on different animals. Several epidemiological studies were conducted to find out the relation of saccharin with cancer promotion. But, no significant association was found between saccharin intake and cancer in humans. It was found that urinary bladder cancer is a high dose phenomenon and is species specific, which occurs only in rats. Lastly, in 2000, Saccharin was removed from the list of human carcinogens by National Toxicology Programme, USA and International Agency for Research on Cancer (IARC). In this article, an effort has been made to study the historical and toxicological aspects of saccharin.